Perbandingan Konsep Keadilan Restoratif Pada Pelaku Anak Di Indonesia Dan Jerman: Comparison of the Concept of Restorative Justice for Child Offenders in Indonesia and Germany - Muhammad Noval Amaldy; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
This research explores the application of restorative justice for juvenile offenders in Indonesia and Germany, focusing on two cases: the AQJ case in Indonesia and a rape case in Germany involving minors. Restorative justice is applied with the aim of protecting the rights of both the children and the victims within the legal process. The study adopts a normative comparative legal approach. There are two main research questions: first, the differences and similarities in the concept of restorative justice for juveniles in Indonesia and Germany; second, the advantages and disadvantages of applying this concept. The result and conclusion is findings indicate that although Indonesia and Germany share the same goal of restoring the situation for both victims and offenders, as well as mitigating the negative impact on children through mediation, there are differences in the implementation mechanisms. In Indonesia, the approach involves family discussions and focuses on the moral recovery of the child. In contrast, in Germany, juvenile judges play a significant role in educating and rehabilitating the offender through formal and structured mechanisms. Additionally, mediation facilities are more widely available in Germany compared to Indonesia, where the understanding and implementation of restorative justice remain limited.